Perlindungan Hukum Terhadap Anak Sebagai Korban Dalam Tindak Pidana Kekerasan Seksual (Studi Kasus Di Polres Serdang Bedagai) - M. Anwar Hafis Rangkuti; Riswan Munthe; Abdul Lawali Hasibuan (Universitas Medan Area, 2022)
Child sexual abuse is a form of child abuse in which an adult or older teenager uses a child for sexual stimulation. Forms of child sexual abuse include soliciting or pressuring a child to engage in sexual activity. Law enforcement in Indonesia at this time cannot be separated from the aspect of legal protection for children. Talks about children and their protection will never stop throughout the history of life, because children are the next generation of the nation and the successor of development, namely the generation that is prepared as the subject of the implementation of sustainable development and the holder of control over the future of a country. Efforts to protect children must be started as early as possible, so that in the future they can participate optimally for the development of the nation and state. The problems discussed in this thesis are about the form of legal protection for child victims of sexual crimes and the Constraints of the Serdang Bedagai Police in Handling Criminal Cases of Sexual Violence Against Children. The type of research in this thesis is normative juridical, namely a research method that examines the study of documents, which uses various secondary data such as legislation, legal theory and can also be in the form of opinions of scholars. The results of this study are forms of legal protection for child victims of sexual crimes regulated in Law Number 35 of 2014 concerning Child Protection, Law Number 23 of 2004 concerning the Elimination of Domestic Violence, Law Number 11 of 2012 concerning the Judicial System Child Crime. The constraint of the Serdang Bedagai Police in Dealing with the Criminal Case of Sexual Violence Against Children is the victim's statement that is not frank, the victim does not tell about the actual witness and the victim's information is always changing so this is confusing in the investigation process and the victim does not give testimony because of threats from the public. certain parties or fear that their disgrace will be known by many people.